Marketing planning of urban development: the theoretical bases of practical use - Petro Hudz (Cхід)
Theoretical aspects of marketing management functions on the basis of planning. Proposed approaches to practical implementation of marketing principles in marketing products, including information. This allows you to identify promising directions and priorities of a marketing plan for the city